Micro Estimates of Public Spending Demand Functions and Tests of the Tiebout and Median-Voter Hypotheses - Gramlich, Edward M.; Rubinfeld, Daniel L. (Journal of Political Economy, 1982)
Responses to questions given to a random sample of Michigan households are used to estimate public spending demand functions. While income and price elasticities are similar to those obtained from aggregate data, positive income elasticities appear to arise because public services are distributed in a prorich manner. A relatively small variance in spending demands among urban and suburban communities in metropolitan areas with substantial public service variety suggests that the Tiebout mechanism works. This interpretation is supported by the fact that actual spending conforms substantially to desired levels in urban areas, but less so in rural areas with little public sector choice.